Design and Analysis of Various Stator Shape Configurations in Dual Rotor Permanent Magnet Flux Switching Motor - Mohd Sungip, Fitri Muhaimin; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2023)
The dual-rotor permanent magnet flux-switching machine (PMFSM) consists of a single stator shared by an inner rotor and an outer rotor. The direction and magnitude of the magnetic field can be altered by varying the current flowing through the switched flux rotor's windings. Because conventional PMFSM machines frequently have flux weakening capabilities and constant power operating regions that are undesirable for wide-range speed applications, variable flux permanent magnet machines are reported as an existing solution. This paper provides the design and performance analysis of a dual rotor PMFSM using a variety of shape configurations. In this paper, there are three designs utilizing wedge-shaped PMFSM, radial-shaped PMFSM, and rectangular-shaped PMFSM is proposed. JMAG-finite Designer's 18.0 element analysis is used in this paper where for all drawing procedure design, it uses the JMAG Editor while for analyze procedure for material, condition and properties setting use the JMAG Designer. The motor's cogging torque, flux linkage, flux distribution, and back-EMF are examined, followed by a load study that examines the motor's torque-speed characteristics and output power with various stator shape configurations. The analysis shows that rectangular shape PMFSM outperforms PMFSM with wedge shape configuration and radial shape configuration in terms of high average torques and power. Future possible attempt also includes optimizing the design parameter and efficiency analysis for all three design of dual rotor permanent magnet flux switching motor.